PENGARUH STOCK SELESCTION SKIIL, MARKET TIMING ABILITY, TURNOVER RATIO DAN CASH FLOW TERHADAP KINERJA REKSA DANA SYARIAH: (Studi Kasus Pada Perusahaan Reksa Dana Syariah yang Terdaftar di OJK Periode Tahun 2011-2014) - Mega Mustika Sari; Sri Mulyati; Estu Widarwati (STIESA Press, 2019)
Mutual funds syariah are other investment opportunities with measurable risk and return is high enough with enough capital affordable to the community. Mutual funds syariah have an Investment Manager with the ability and knowledge of the market it is or will happen. Therefore, mutual funds syariah selected by investors because it is cheap, easy and